Optimization of physical energy and velocity allocation for cyclists in road cycling individual time trial using genetic algorithm - Li, Xinyu; Zou, Benxu; Wang, Xin; Liu, Chaoran (Frontiers in Physiology, 2025)
IntroductionEffective energy management for optimizing energy and speed allocation for athletes in road cycling individual time trials is crucial due to the race’s long distances. Existing strategies often consume excessive body energy due to inadequately addressing the impact of slopes and curves.MethodsWe propose an advanced energy allocation strategy using a genetic algorithm. Our research focuses on optimizing speed and energy allocation specifically in curves and on slopes given factors such as air resistance, friction, gravity and weather to maximize athletes’ energy efficiency during time trials. For curve optimization, we optimize the athletes' cornering strategies based on the parameters including road width, inner curve radius and curve angles.ResultsThe simulation results demonstrate that time is reduced by 9.7% on a standard 400-m track and time is reduced by 6.35% on bridge testing comparing with pre optimization strategies.DiscussionWe validate the optimizing strategy based on the 2024 Paris Olympic Games road cycling individual time trial course, which demonstrates the effectiveness of the strategy. This research provides athletes with valuable guidance for optimal energy distribution.